2018
DOI: 10.2478/hukin-2018-0047
|View full text |Cite
|
Sign up to set email alerts
|

Moral Behavior in the Locker Room Predicts Perceptions of Task Cohesion in Youth Ice Hockey Player

Abstract: Task cohesion (i.e., perceptions of team unity towards a task goal and positive feelings towards one’s own involvement) is associated with myriad psychosocial benefits for youth athletes. Accordingly, sport researchers and youth sport stakeholders are interested in ways of fostering task cohesion. Recent work has found evidence that prosocial and antisocial behaviors among teammates are associated with athletes’ perceptions of task cohesion; however, this research has been limited to moral behavior that takes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Pizzi and Stanger (2019) also found out that ethical behaviors toward teammate players as well as opponent players improve team performance and efficiency. On the other hand, Graupensperger et al (2018) found out that ethical behaviors lead to greater coherence of teammate players in ice hockey players, and also reduce antisocial behaviors in them. Simon (2016) also examined ethical issues in the Turkish sports media in his research, and the research results showed that the sports media have not been loyal to ethical codes and repeatedly violated ethical codes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pizzi and Stanger (2019) also found out that ethical behaviors toward teammate players as well as opponent players improve team performance and efficiency. On the other hand, Graupensperger et al (2018) found out that ethical behaviors lead to greater coherence of teammate players in ice hockey players, and also reduce antisocial behaviors in them. Simon (2016) also examined ethical issues in the Turkish sports media in his research, and the research results showed that the sports media have not been loyal to ethical codes and repeatedly violated ethical codes.…”
Section: Introductionmentioning
confidence: 99%
“…Ethical behaviors also lead to greater coherence(Graupensperger and Tisak, 2018, Bermejo et al, 2018). Therefore, in general, the sports managers and sports referees in Iran are recommended to use the principles of the present code in order to improve the ethical factors in the sports environment.Another result of the present research was to observe respect as one of the pillars of the refereeing ethics regulations in sports.…”
mentioning
confidence: 99%